Extragalactic Radio Sources 1996
DOI: 10.1007/978-94-009-0295-4_133
|View full text |Cite
|
Sign up to set email alerts
|

Unified Schemes for Extragalactic Radio Sources

Abstract: My own suspicion is that the universe is not only queerer than we suppose, but queerer than we can suppose -J.B.S. Haldane OverviewThis review aims to provide the background and current perspective of some of the striking asymmetries exhibited by extragalactic double-lobed radio sources, paying special attention to the reported interrelationships among some of them. The asymmetries addressed here are related not only to the jets, and we particularly aim to highlight some less discussed aspects pertaining to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 133 publications
(158 reference statements)
2
54
0
Order By: Relevance
“…An alternative model is that the jet interacts at the flare point with some large-scale external feature that is able to affect the whole jet. Gopal-Krishna & Saripalli (1984) have pointed out the coincidence between the radio and X-ray flare point and an optical 'shell', seen in deep images, which they consider to be a remnant of a cannibalized galaxy. A series of shocks caused by such an interaction would be equally consistent with what we observe, if they can be distributed over the entire region of X-ray emission or, again, if the magnetic field is sub-equipartition.…”
Section: Discussion : T H E O R I G I N O F T H E F L a R E mentioning
confidence: 99%
“…An alternative model is that the jet interacts at the flare point with some large-scale external feature that is able to affect the whole jet. Gopal-Krishna & Saripalli (1984) have pointed out the coincidence between the radio and X-ray flare point and an optical 'shell', seen in deep images, which they consider to be a remnant of a cannibalized galaxy. A series of shocks caused by such an interaction would be equally consistent with what we observe, if they can be distributed over the entire region of X-ray emission or, again, if the magnetic field is sub-equipartition.…”
Section: Discussion : T H E O R I G I N O F T H E F L a R E mentioning
confidence: 99%
“…As ex-pected, there is very little difference between the two distributions, with the only exception being a steepening in the rest frame for three sources in the sample with flattening SEDs. Whilst many authors have shown that a k-correction is a credible explanation for the z-α correlation (Gopal-Krishna 1988;Lacy et al 1993;Carilli et al 1999), some of these same studies also show that an apparent -yet weaker -correlation still exists between redshift and rest-frame (k-corrected) radio spectral index (Lacy et al 1993; Blundell et al 1999;Carilli et al 1999). These samples were all selected at frequencies in the range 38 ν 408 MHz, at least a factor of 3 lower in finding frequency than the SUMSS-NVSS USS sample, and at least an order of magnitude brighter in radio luminosity.…”
Section: A K-correctionmentioning
confidence: 99%
“…Different models exist that explain variability in jet emission, for example through lighthouse effects (see e.g. Gopal-Krishna & Wiita 1992), shock fronts in jets (see e.g. Marscher & Gear 1995;Marscher et al 2008) or certain physical conditions in the jet plasma (see e.g.…”
Section: Introductionmentioning
confidence: 99%